Arthroscopic Cortical-Button Latarjet Procedure for Anterior Shoulder Instability With Glenoid Bone Loss - Nicolas Bonnevialle MD, PhD; Valentin Massin MD; Mathieu Girard MD; Yoann Dalmas MD (SAGE Publishing, 2022)
Background: The Latarjet procedure is a common treatment of anterior shoulder instability associated with glenoid bone loss. Advanced arthroscopic technique provided a safe cortical-button fixation of the coracoid process transferred onto the glenoid neck combined with a Bankart repair. Indications: This is an 18-year old woman, complaining of recurrent right shoulder dislocation and subluxation, which made her unable to play handball at competitive level. Physical examination confirmed anterior apprehension without hyperlaxity. Computed tomography (CT) scan identified a Hill-Sachs lesion and a glenoid bone loss of 11%. Instability Severity Index Score was calculated at 7 points. Technique Description: Patient was placed in a beach-chair position under general anesthesia combined with an interscalene nerve block. A 70° scope and specifically designed instruments were used. The technique required 5 steps: (1) coracoid preparation: pectoralis minor and coracoacromial ligament release, flattening of the undersurface, positioning of the peg button, and osteotomy of the coracoid; (2) glenoid preparation: flattening of the neck of the scapula, insertion of 2 anchors (3 and 6 o'clock), and glenoid drilling with a specific guide; (3) subscapularis split: use of an intra-articular and extra-articular spreader splitting the subscapularis muscle at the level of the glenoid wire (shoulder in neutral rotation) and opening of a "safe window"; (4) fixation step: transfer of the coracoid through the subscapularis split with shuttle suture and permanent fixation with a posterior cortical button (compression controlled at 100 Newtons with a dynamometer); and (5) Bankart repair. The shoulder was protected in a sling 4 weeks, and external rotation recovery was allowed at 6 weeks. Results: Favorable outcomes were reported at 6 months of follow-up without any complication. Full range of motion with limited external rotation deficit was obtained and a negative apprehension test. Radiologic assessment confirmed graft incorporation at 6 months, allowing return to overhead sports at a competitive level. Discussion/Conclusion: Arthroscopic cortical-button Latarjet procedure is a safe option to treat anterior shoulder instability associated with glenoid bone loss in patient with high demand sports. The procedure is safe and combine bone graft and Bankart repair. Using a cortical button fixation avoids screw related complications.